Spectrophotometric Determination, Analysis And Validation Of Acyclovir 0n Solid Dosage Form - Wisam T. Hammadi; Sarhan A. Salamn (International Journal of Medicine and Health, 2024)
A new, economical, sensitive, simple, rapid UV spectrophotometric method has been developed for the estimation of Acyclovir in pure form and pharmaceutical formulation. This UV method was developed using NaOH (0.1N) as a solvent. In the present method, the wavelength selected for analysis was 253nm. Using 1cm match quartz cells, all of the spectrum and absorbance measurements were performed using an UV-VIS spectrophotometer (Shimadzu 1800) was used to carry out the spectral analysis. The ICH guidelines were used to validate the method. Throughout the study, we compared the purity of the drugs, with standard drugs (HPLC grade purity >99%) purchased from SIGMA ALDRICH Ltd. The test drugs from pharmaceutical companies (CIPLA) in its dosage form taken from the market.The method was validated for linearity, range, accuracy, precision, drug content , LOD and LOQ. Linearity was found in the range of 2.5-40μg/ml. Accuracy was performed by using a recovery study. The percentage recovery for all the methods performed was in the range of 99-100% indicating of zero interference of the excipients (in the formulation). LOD and LOQ were found to be 1.5766434 and 4.7777075 respectively [SD: 0.474474135; SE: 0.212191284]. Relative error (<2) values showed that the proposed procedure exhibited excellent Interday and intraday precision.The proposed UV spectroscopic method was found to be accurate, precise, stable, linear, specific, and simple for quantitative estimation of acyclovir in bulk and pharmaceutical dosage form. Hence the present UV spectroscopic method is suitable for the routine assay of acyclovir in bulk and pharmaceutical formulations.